2003
DOI: 10.1139/x02-157
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of flowering inEucalyptus nitensby paclobutrazol was enhanced by nitrogen fertilizer

Abstract: Abstract:We examined the effects of nitrogen and phosphorus fertilizer and paclobutrazol on flowering precocity and abundance in Eucalyptus nitens Deane & Maid. Trials to test these effects consisted of a factorial nitrogen by phosphorus experiment replicated on two sites and factorial nitrogen by paclobutrazol experiments conducted separately on reproductively immature and reproductively mature trees. The increase in tree size due to nitrogen fertilization increased the occurrence and abundance of precocious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
2
17
0
2
Order By: Relevance
“…These results showed that PBZ inhibited the tree growth. Previous research also reported that PBZ resulted in plant height reduction (Ahmad Nazarudin 2012;Gent 2004;Pinto et al 2005;Taiz & Zeiger 2006;Williams et al 2003).…”
Section: Resultsmentioning
confidence: 92%
“…These results showed that PBZ inhibited the tree growth. Previous research also reported that PBZ resulted in plant height reduction (Ahmad Nazarudin 2012;Gent 2004;Pinto et al 2005;Taiz & Zeiger 2006;Williams et al 2003).…”
Section: Resultsmentioning
confidence: 92%
“…But, whether the previous year's fertilisation increased precocity is still under discussion. No effect was found on burst for vegetative buds (Floistad 2002 on conifers), but flowering was advanced on eucalyptus (Williams et al 2003) and apple (Wojcik and Klamkowski 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Wiltshire et al (1998), on the other hand, found a moderate genetic control for early flowering but only a weak genetic relationship between this trait and growth within and between populations of Eucalyptus. Williams et al (2003) also found that early flowering could also affect the growth and the development of trees, although in their study early flowering was artificial promoted, rather than a genetically determined. Data presented in this paper indicate that selection for precocity may significantly enhance both growth and survival (Table 3).…”
Section: Traitsmentioning
confidence: 95%